Computational Thermochemistry of Six Ureas, Imidazolidin-2-one, N,N '-Trimethyleneurea, Benzimidazolinone, Parabanic Acid, Barbital (5,5 '-Diethylbarbituric Acid), and 3,4,4 '-Trichlorocarbanilide, with an Extension to Related Compounds - Juan Z Davalos (2010)
A computational study of the structural and thermochemical properties of N-phenyl (open) and N-alkyl (cyclic) ureas, through the use of M05-2X and B3LYP density functional theory calculations has been carried out. The consistency of the literature experimental results has been confirmed, and using mainly isodesmic reactions, the unknown Delta fH(0)(g) of the other urea derivatives were estimated. The experimental results together with the theoretical information have permitted the study of the effect of phenyl, p- and m-chlorophenyl, alkyl, and carbonyl substitutions on the thermodynamical stability of urea and its cyclic derivatives. The peculiar behavior of the N-tert-butyl substituent in cyclic ureas has been related to geometric deformations.